Effects of acute ingestion of sodium citrate on metabolism and 5-km running performance: A field study - Ööpik, V.; Saaremets, I.; Timpmann, S.; Medijainen, L.; Karelson, K. (Canadian Journal of Applied Physiology, 2004)
The purpose of the study was to (a) assess the effects of sodium citrate ingestion on metabolism and performance capacity in a 5-km competitive outdoor stadium run in trained male runners, and (b) elucidate the potential relationship between citrate-induced changes in plasma volume, body mass, and performance. Ten subjects (age 22.1 ± 2.5 yrs, body mass 74.1 ± 6.1 kg, height 180.1 ± 5.7 cm, VO2max 60.8 ± 5.5 ml·kg-1·min-1) participated in the study. There was no effect of treatment on 5-km running time: 1100.0 ± 79.1 and 1082.7 ± 62.0s in citrate (CIT) and in placebo (PLC) trials, respectively, p = 0.09. Blood pH increased from 7.34 ± 0.07 to 7.49 ± 0.07 (p = 0.002) as a result of administering sodium citrate in the amount of 0.5 g·kg-1 body mass in 1.5 litres of solution but remained stable while the equal volume of placebo drink was consumed: 7.40 ± 0.04 and 7.44 ± 0.09. The relative change in plasma volume after administering the drink was -1.99 ± 3.49% in the PLC and 9.75± 6.51% in the CIT trial (p = 0.001). Body mass did not differ before drinking; however, before the start the subjects were heavier in the CIT trial (74.2 ± 6.1 kg) vs. the PLC trial (73.4 ± 6.2 kg, p = 0.048). The shifts in plasma volume and body mass were not related to changes in performance. The results suggest that ingestion of sodium citrate induces an increase in water retention, plasma volume, and blood pH before exercise but does not improve performance in a 5-km competitive run in field conditions in trained male runners.